6C overcharge artificial graphite negative electrode material and preparation method and application thereof
By using 6C supercharging artificial graphite negative electrode material in lithium-ion batteries, the problems of battery polarization and energy utilization limitation during fast charging are solved, high energy density and stable performance are achieved, and the fast charging needs of electric vehicles are met.
Patent Information
- Application Number
- CN202411631988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
During the fast charging process, existing lithium-ion batteries have problems such as increased battery polarization, limited energy utilization, capacity attenuation and excessive heat, which limits the charging time of electric vehicles and affects battery performance and safety.
A 6C supercharging artificial graphite negative electrode material was developed, and the pretreated coke raw materials were coated with solvent method and in-situ polymerization coating, combined with pyrolytic granulation and microwave graphitization treatment, and a material with high specific capacity, excellent cycle stability and good rate performance was prepared.
It realizes the high energy density and stable performance of lithium-ion batteries during fast charging. After 3,000 cycles, the discharge capacity retention rate reaches more than 80%, meeting the requirements of 6C charging without lithium degradation, and improving the safety and adaptability of the battery.
Smart Images

Figure CN119542381A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a 6C supercharged artificial graphite negative electrode material and a preparation method and application thereof, belonging to the field of new energy and new material batteries. Background Art
[0002] With the rapid development of the electric vehicle market, the requirements for the energy density and charging speed of lithium-ion batteries are increasing. Traditional high-energy-density lithium-ion batteries have significant technical bottlenecks in fast charging, mainly manifested in increased battery polarization, limited energy utilization, increased capacity decay, and excessive heat generation during charging. These problems not only limit the charging time of electric vehicles, but also have an adverse effect on the performance and safety of the battery. Therefore, the development of lithium-ion battery technology that can achieve both high energy density and efficient and fast charging has become a hot topic in current research.
[0003] Existing high energy density lithium-ion batteries mainly use graphite as the negative electrode material. Graphite negative electrode materials have high energy density and stable cycle performance, but there are problems of uneven reaction current and irreversible lithium plating during fast charging, which leads to a decrease in battery performance. In addition, although hard carbon materials show excellent rate performance, their initial coulombic efficiency is low and their energy density is not as good as graphite. Therefore, the use of graphite or hard carbon materials alone is difficult to meet the dual needs of high energy density and fast charging. Therefore, the research and development of the invention of 6C supercharged artificial graphite negative electrode materials is of great significance to promote the rapid development of the electric vehicle industry. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems existing in the prior art, the first object of the present invention is to provide a 6C super-charged artificial graphite negative electrode material.
[0005] A 6C supercharged artificial graphite negative electrode material, comprising: The gram capacity of the 6C supercharged artificial graphite negative electrode material is greater than 330mAh / g; the compaction density of the electrode is ≥1.60g / cc; 10%~80% SOC meets 6C charging without lithium precipitation; after 3000 cycles, the discharge capacity retention rate is ≥80%.
[0006] A 6C supercharged artificial graphite negative electrode material, comprising at least one of the following features: The gram capacity of the 6C supercharged artificial graphite negative electrode material is >350mAh / g; The pole piece compaction density is greater than 1.80 g / cc; When the 6C supercharged artificial graphite negative electrode material is cycled 3000 times, the discharge capacity retention rate is greater than 86%; The initial efficiency of the 6C supercharged artificial graphite negative electrode material is >93%; The specific surface area of the 6C supercharged artificial graphite negative electrode material is 0.5~3m 2 / g; The particle size D50 of the 6C supercharged artificial graphite negative electrode material is 5-13 μm; The sphericity of the 6C supercharged artificial graphite negative electrode material is greater than 0.85; The graphitization degree of the 6C supercharged artificial graphite negative electrode material is ≥94%.
[0007] The second object of the present invention is to provide a method for preparing a 6C supercharged artificial graphite negative electrode material.
[0008] The second technical purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for preparing a 6C supercharged artificial graphite negative electrode material, which specifically comprises the following steps: The 6C supercharged artificial graphite negative electrode material is prepared by using the pretreated charred raw material through solvent coating and in-situ polymerization coating composite coating, and then through graphitization post-treatment.
[0009] The gram capacity of the 6C supercharged artificial graphite negative electrode material is ≥355mAh / g; the electrode compaction is ≥1.60g / cc; 10%~80% SOC meets 6C charging without lithium precipitation; when the number of cycles reaches 3000 times, the discharge capacity is not less than 80% of the initial capacity.
[0010] Preferably, the coke-like raw material includes at least one of petroleum coke, needle coke, asphalt coke or anthracite; Preferably, the pretreatment includes airflow milling treatment, wherein the feed rate of the raw material is 20-50 kg / h, the gas pressure in the mill chamber is 0.6-0.8 MPa, the gas temperature in the mill chamber is 150-250°C, the nozzle airflow velocity is 1200-1800 m / s, and the classifying wheel speed is 8000-12000 rpm; Preferably, the D50 of the pretreated charred raw material is 3-10 μm.
[0011] Further preferably, the coke-like raw material pretreatment comprises: Select high-purity, high-crystallinity coke-like raw materials as the basic raw materials, add an appropriate amount of conductive particles, use airflow grinding technology to crush the raw materials to micron level, remove large particles and impurities through screening process, and obtain the precursor with the required particle size; Preferably, the conductive particles include at least one of carbon nanotubes, conductive carbon black, acetylene black, graphite particles, graphene, metal powder or carbon fiber species.
[0012] Preferably, the solvent coating process comprises: The coating material is dissolved in an organic solvent to form a uniform coating solution, the precursor material obtained by pretreatment of the raw material is added to the coating solution, and the solvent is evaporated by stirring so that the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer on the surface of the precursor particles.
[0013] Further, the coating material is sodium polystyrene sulfonate; Further, the organic solvent includes at least one of deionized water, N-methylpyrrolidone or dimethylformamide; Furthermore, the mass ratio of the coating material to the solvent is 1:(10-20); Furthermore, the uniform coating thickness is: 10~20nm; Furthermore, the mass ratio of the precursor particles to the coating solution is (2-5):1.
[0014] Preferably, the preparation process of the coating material comprises: Styrene monomer and sodium sulfonate styrene monomer are mixed and polymerized in an initiator system to obtain a sodium polystyrene sulfonate product.
[0015] Furthermore, the mass ratio of the styrene monomer to the sodium sulfonate styrene monomer is: (3-6): 1; Further, the initiator comprises at least one of benzoyl peroxide or azobisisobutyronitrile; Furthermore, the polymerization reaction temperature is: 60-85°C; Furthermore, the polymerization reaction time is 3 to 6 hours.
[0016] Preferably, the in-situ polymerization coating process comprises: The product coated by the solvent method is first subjected to oxidation treatment, and then added to a polymerization system containing phenolic and aldehyde compounds to initiate in-situ polymerization; and then a curing agent is added for curing treatment to obtain an in-situ polymerization coated product.
[0017] Further, the reagent used in the oxidation treatment includes H2O2; The H2O2 stirring speed: 200-500 rpm; Further, the phenolic compound includes at least one of phenol, diphenol, naphthol, and cresol; Further, the aldehyde compound includes at least one of formaldehyde, furfural, benzaldehyde, and isobutyraldehyde; Furthermore, the stirring speed of the phenol solution is 200 to 500 rpm; Furthermore, the phenol solution is stirred for 10 to 60 minutes; Furthermore, the stirring time after the formaldehyde solution is added is 0.5 to 2 hours; Furthermore, the mass ratio of the product coated by the solvent method to the oxidant for oxidation treatment is: (1-4): 1; Furthermore, the thickness of the in-situ polymerized coating layer is: 20~90nm; Furthermore, the mass ratio of the solution of the phenolic compound to the product coated by the solvent method is: 1:(3-6); Furthermore, the polymerization system further comprises an initiator, specifically an acidic or basic initiator; Furthermore, the acidic initiator includes inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, and oxalic acid, and the alkaline catalyst includes ammonia, sodium carbonate, sodium hydroxide, and the like.
[0018] Further, the curing agent includes at least one of hexamethylenetetramine, diethylaminopropylamine, trimethylhexamethylenediamine, and dihexyltriamine; Furthermore, the mass ratio of the curing agent to the product coated by the solvent method is: (0.1~0.4):1.
[0019] Preferably, the graphitization post-treatment process comprises: The composite coated product is first subjected to pyrolysis granulation, then additives are added, secondary granulation is performed at high temperature, followed by spheroidization shaping, and finally graphitization treatment is performed to obtain 6C supercharged artificial graphite negative electrode material; Further preferably, the temperature curve in the pyrolysis granulation is: the first part has a heating rate of 5-8°C / min, an end temperature of 200-250°C, and stirring for 1-4h; the second part has a heating rate of 5-8°C / min, a key temperature of 400-500°C, and stirring for 2-8h; Further, the additive includes at least one of carbon nanotubes, conductive carbon black, asphalt or phenolic resin; Furthermore, the mass ratio of the additive to the composite coated product is: (0.05-0.2): 1; Furthermore, the temperature curve of the secondary granulation is: the first part has a heating rate of 7-10°C / min, an end temperature of 100-150°C, and stirring for 1-4h; the second part has a heating rate of 7-10°C / min, a key temperature of 200-300°C, and stirring for 1-4h; Furthermore, the ball milling speed of the mechanical ball milling is 250-400 rpm, the ball milling time is 1-4 hours, and the ball-to-material ratio is (3-6):1; Furthermore, the graphitization treatment includes microwave graphitization treatment; preferably, in the microwave graphitization, the microwave frequency is: 2~3GHz, the microwave initial power is: 600~800W, the heating time (initial) is: 30~60min, the microwave power (latter) is: 1000~1500W, the heating time (later) is: 1~3h, and the graphitization temperature is 2800~3200℃.
[0020] Preferably, the ratio of the particle size D50 of the 6C super-charged artificial graphite negative electrode material to the pre-treated coke-like raw material D50 is 1-2.
[0021] The present invention prepares a 6C supercharged artificial graphite negative electrode material, which has the advantages of high specific capacity, excellent cycle stability, good rate performance, etc., and also has the characteristics of good safety performance, environmental protection, wide adaptability, etc., and has a very broad application scenario.
[0022] The third object of the present invention is to provide an application of a 6C supercharged artificial graphite negative electrode material.
[0023] The third technical objective of the present invention is achieved through the following technical solutions: A negative electrode sheet comprises a negative electrode material prepared from the 6C supercharged artificial graphite negative electrode material.
[0024] A lithium ion battery comprises the negative electrode sheet.
[0025] An energy storage device, the electrochemical device comprising the lithium-ion battery.
[0026] In summary, the beneficial effects of the present invention are: 1. The 6C supercharged artificial graphite negative electrode material prepared by this method has the advantages of gram capacity>330mAh / g; pole piece compaction ≥1.60g / cc; 10%~80% SOC meets 6C charging without lithium precipitation; when the number of cycles reaches 3000 times, the discharge capacity is not less than 80% of the initial capacity; 2. In this method, the raw material selection is diverse, and a variety of carbon precursors such as anthracite, needle coke, petroleum coke, asphalt, etc. are used. These raw materials are widely available and cost-controlled, providing a rich choice for the preparation of high-performance artificial graphite; precise particle size control: through advanced processes such as air flow milling, the raw material particle size is precisely controlled at the micron level, which is conducive to the uniformity and consistency of the subsequent granulation and graphitization process; 3. In this method, the solvent method is used for preliminary coating. The solvent method has high coating uniformity and can form a uniform and dense coating layer on the surface of graphite particles, significantly improving the electrochemical properties of the material. By adjusting the type, concentration, temperature and other parameters of the solvent, the thickness and uniformity of the coating layer can be accurately controlled; 4. In this method, in-situ polymerization coating is used for composite coating. Through the in-situ polymerization reaction, the coating material can form a strong chemical bond on the surface of the graphite particles, improve the stability and durability of the coating layer, and further enhance the electrochemical performance of the graphite negative electrode material; 5. In this method, the compaction density and processing performance of the graphite negative electrode material are improved by pyrolysis granulation, which is beneficial to improving the energy density and safety of the battery; through the secondary granulation process, small-grain graphite can be further granulated into larger particles, while maintaining the high rate performance of small particles and the high compaction density of large particles. The graphite negative electrode material after secondary granulation has higher liquid retention performance and lower expansion coefficient, thereby improving the material's cycle performance and fast charging performance; it can significantly improve the comprehensive performance of graphite negative electrode materials and meet the needs of high-end power batteries for fast charging, high energy density and long cycle life; 6. In this method, microwave heating is fast and uniform through microwave graphitization post-treatment, which can significantly improve the heating efficiency of the graphitization process; compared with the traditional graphitization process, microwave graphitization can shorten the processing time, reduce energy consumption and production costs; make the graphitization process more complete and uniform, improve the crystallinity and graphitization degree of artificial graphite, and thus improve its electrochemical properties.
[0027] Therefore, the 6C supercharged artificial graphite negative electrode material provided by the present invention has the advantages of high specific capacity, excellent cycle stability, good rate performance, etc., and also has the characteristics of good safety performance, environmental protection, wide adaptability, etc., and has a very broad application scenario. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a preparation flow chart of 6C supercharged artificial graphite negative electrode material.
[0029] Figure 2 This is a SEM image of the artificial graphite negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0030] To make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] The present invention provides a preparation process of a 6C supercharged artificial graphite negative electrode material, which specifically comprises the following steps: Step (1) Pretreatment of coke-like raw materials High-purity, high-crystallinity petroleum coke and needle coke are selected as basic raw materials, acetylene black is added as conductive particles, and the raw materials are crushed to micron level using air flow grinding technology. Large particles and impurities are removed through a screening process to obtain a precursor of the required particle size.
[0032] Step (1) pretreatment of coke-like raw materials includes the following steps: taking high-purity, high-crystallinity petroleum coke and needle coke as basic raw materials in a mass ratio of 1:1, adding 5-10wt% or any value in the range of acetylene black as conductive particles, using airflow milling technology to crush the raw materials to micron level, removing large particles and impurities through a screening process, and obtaining a precursor with a desired particle size. In the airflow milling technology, the raw material feed rate is 20-50 kg / h or any value in the range, the gas pressure in the milling chamber is 0.6-0.8 MPa or any value in the range, the gas temperature in the milling chamber is 150-250°C or any value in the range, the nozzle gas velocity is 1200-1800 m / s or any value in the range, the classifying wheel speed is 8000-12000 rpm, and the precursor particles prepared by screening have a particle size D50 of 3-10 μm or any value in the range.
[0033] In this method, pure and high-crystallinity petroleum coke and needle coke are selected as basic raw materials to ensure the purity and crystallinity of the final product, thereby improving its electrochemical performance. High purity means less impurity content, which helps to reduce the self-discharge and side reactions of the battery; high crystallinity is conducive to the insertion and extraction of lithium ions, improving the specific capacity and cycle stability; adding acetylene black as conductive particles can significantly improve the conductivity of graphite negative electrode materials. Acetylene black has excellent conductivity and liquid absorption, which can increase the electron transmission channel inside the material, reduce internal resistance, and improve the charge and discharge efficiency and power density of the battery; the addition of high-purity, high-crystallinity raw materials and conductive particles, as well as precise particle size control, jointly improve the electrochemical properties of graphite negative electrode materials. Including specific capacity, cycle stability, rate performance and other aspects have been improved, making it more suitable for the application requirements of high-end power batteries; micron-sized precursor particles have better processing performance, which is conducive to the smooth progress of subsequent granulation and graphitization processes. By regulating the relationship between the particle size of the particles after crushing and the particle size of the final product, within a limited range, the obtained negative electrode material product exhibits better electrochemical performance.
[0034] Step (2) Solvent coating preparation S21 takes styrene monomer and sodium sulfonate styrene monomer as raw materials and mixes them uniformly in a solvent according to a certain mass ratio; S22: adding an appropriate amount of benzoyl peroxide or azobisisobutyronitrile to the mixed monomers, and continuously stirring at a suitable temperature to cause a polymerization reaction. After the reaction is completed, the product is subjected to post-treatment steps such as washing and drying to remove unreacted monomers and impurities to obtain a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone to form a uniform coating solution; S33: adding the precursor material obtained by pre-treatment of the raw materials into the coating solution, and volatilizing the solvent by stirring so that the coating material is uniformly adsorbed on the surface of the precursor particles, thereby forming a uniform coating layer on the surface of the precursor particles.
[0035] Step (2) preparation of the coating solution comprises the following steps: S21 mixing styrene monomer and sodium sulfonate styrene monomer in a mass ratio of (3-5): (3-5) (or any ratio within a range) as raw materials, wherein the solvent used comprises NMP, and the volume ratio of styrene to solvent is 4-6:1 or any value within a range; S22 adding an appropriate amount of (6-8) wt% or any value within a range of benzoyl peroxide and (6-8) wt% or any value within a range of azobisisobutyronitrile to the mixed monomers, and continuously stirring at a temperature of 80-120° C. to cause a polymerization reaction, after the reaction is completed for 3-6 hours, washing, drying and other post-treatment steps are performed on the product to remove unreacted monomers and impurities to obtain a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone in a mass ratio of (3-5):1 (or any ratio within a range) to form a uniform coating solution.
[0036] In this method, the use of solvent coating can ensure that the coating material (sodium polystyrene sulfonate) forms a uniform and dense coating layer on the surface of the graphite particles. This uniformity is crucial to improving the electrochemical performance of the negative electrode material because it helps to reduce the direct contact between the electrolyte and the graphite surface, thereby reducing the irreversible capacity and interface resistance; sodium polystyrene sulfonate, as a polymer material, has good chemical stability and thermal stability. This stability enables the coating layer to maintain its structure and performance during the battery charging and discharging process, and is not prone to falling off or degradation, thereby extending the service life of the battery; the introduction of sodium sulfonate groups makes sodium polystyrene sulfonate have a certain conductivity, which helps to improve the overall conductivity of the graphite negative electrode material, reduce the internal resistance of the battery, and improve the charging and discharging efficiency; the sodium polystyrene sulfonate coating layer can improve the thermal stability of the graphite negative electrode material, reduce the risk of thermal runaway of the material under high temperature conditions, and improve the safety of the battery.
[0037] Step (3) In-situ polymerization coating S31 adding the solvent-coated graphite particles into H2O2 and stirring rapidly; S32 adding the oxidized graphite particles into the phenolic substance solution, heating and stirring, so that the phenol and the graphite surface are fully infiltrated; S33 then adds aldehyde substances and initiators to initiate an in-situ polymerization reaction of the phenolic resin, completely covering the end faces and active points on the graphite surface; S34 Finally, a proper amount of hexamethylenetetramine is added to the solution to solidify the phenolic resin. After the solidification is complete, the sample is washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating.
[0038] Step (3) in-situ polymerization coating comprises the following steps: S31 adding the solvent coated graphite particles to 30% H2O2 at a mass ratio of 2:1, stirring at a speed of 200 to 500 rpm for 0.5 to 2 hours; S32 adding the oxidized graphite particles to a 70°C phenol aqueous solution at a concentration of (4 to 6) g / mL or any value within the range at a mass ratio of (4 to 6):1 (or any value within the range), heating at 70 to 100°C, stirring at a speed of 200 to 500 rpm, and heating at a speed of 200 to 500 rpm. rpm, stirring time 10-60min, to make phenol and graphite surface fully infiltrated; S33 then drop formaldehyde solution (37% concentration, 0.5-1.5:1 or any value within the range of phenol molar ratio), if an initiator (such as sodium hydroxide, etc., 0.01-0.05:1 or any value within the range of phenol molar ratio) is added, the in-situ polymerization reaction of phenolic resin is initiated to completely cover the end faces and active points of the graphite surface; S34 finally hexamethylenetetramine is added to the solution to cure the phenolic resin (the addition amount is 10-15wt% of the total amount of polymerization monomers or any value within the range), after complete curing, wash and separate the sample, and dry it to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating.
[0039] In this method, H2O2 as an oxidant can effectively improve the chemical properties of the graphite particle surface, increase its surface active sites, and provide a better adhesion basis for subsequent coating materials. This surface modification enhances the bonding force between the coating layer and the graphite particles, making the coating layer more solid and not easy to fall off; the in-situ composite coating method allows phenol and formaldehyde to directly polymerize on the surface of the graphite particles to form a uniform coating layer. This coating method avoids problems such as uneven coating or coating layer defects that may occur in traditional coating methods, and improves the density and integrity of the coating layer; the uniform and dense coating layer can reduce the direct contact between the electrolyte and the graphite surface, reduce the interface resistance and polarization phenomenon, and thus improve the electrochemical performance of the material. This includes improving specific capacity, cycle stability and rate performance; the coating layer can also improve the thermal stability of the graphite negative electrode material and reduce the risk of thermal runaway of the material under high temperature conditions. At the same time, the uniform coating layer helps to inhibit the volume expansion and contraction of the material during the charge and discharge process, and improve the safety performance of the battery.
[0040] Step (4) Post-graphitization treatment S41: putting the dried coated graphite particles into a reaction kettle, and electrically heating them according to a specific temperature curve under an inert gas atmosphere to perform pyrolysis and granulation; S42 adds an appropriate amount of additives to the primary granulation product, performs secondary granulation under high temperature stirring conditions, and then performs spherical shaping of the particle morphology by mechanical treatment at the end; S43 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts a microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature, and after graphitization is completed, a 6C supercharged artificial graphite negative electrode material is obtained.
[0041] Step (4) graphitization post-treatment comprises the following steps: S41: putting the dried coated graphite particles into a reactor, and in an inert gas atmosphere, performing electric heating for pyrolysis granulation according to the first part heating rate of 5-8°C / min, the end temperature of 200-250°C, and stirring for 1-4h; the second part heating rate of 5-8°C / min, the key temperature of 400-500°C, and stirring for 2-8h; S42: adding carbon nanotubes and asphalt (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.1:1), and performing the heating according to the heating curve: the first part heating rate of 7-10°C / min, the end temperature of 200-250°C, and stirring for 1-4h; the second part heating rate of 5-8°C / min, the key temperature of 400-500°C, and stirring for 2-8h. min, the end temperature is 100~150℃, and stirring is 1~4h; the second part is heated at a rate of 7~10℃ / min, the key temperature is 200~300℃, and stirring is 1~4h for secondary granulation. After the end, the particle morphology is spheroidized by mechanical treatment. The ball milling speed of mechanical ball milling is 250~400rpm, the ball milling time is 1~4h, and the ball-to-material ratio is (3~6):1 or any value within the range; S43 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts the microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization is completed, 6C super-charged artificial graphite negative electrode material is obtained. The microwave frequency is: 2~3GHz, the initial microwave power is: 600~800W, the heating time (initial) is: 30~60min, the microwave power (later) is: 1000~1500W, the heating time (later) is: 1~3h, and the graphitization temperature is 2800~3200℃.
[0042] In this method, during the pyrolysis granulation process, the coating material forms a stable structure on the surface of the graphite particles through high temperature treatment, which enhances the firmness and durability of the coating layer; pyrolysis granulation helps to make the particle size of the graphite particles more uniform, which is conducive to the subsequent process and the performance consistency of the final product; secondary granulation can further adjust the morphology and particle size distribution of the graphite particles to make them more in line with the requirements of high-performance negative electrode materials. Through reasonable particle size design, the rate performance and cycle stability of the negative electrode material can be improved; during the secondary granulation process, the particles are more tightly bound, which improves the compactness of the negative electrode material and helps to improve the volume energy density of the battery; secondary granulation can form more pores and channel structures, which is conducive to the insertion and extraction of lithium ions and improves the electrochemical performance of the negative electrode material; microwave heating can more fully activate the carbon atoms in the graphite particles, promote their transformation to graphite structure, and improve the degree of graphitization. This helps to improve the conductivity, thermal stability and chemical stability of the negative electrode material.
[0043] Example 1
[0044] A preparation process of a 6C supercharged artificial graphite negative electrode material is as follows Figure 1 As shown, specifically including: Step (1) Pretreatment of coke-like raw materials High-purity, high-crystallinity petroleum coke and needle coke are taken as basic raw materials in a mass ratio of 1:1, and 5wt% of acetylene black is added as conductive particles. The raw materials are crushed to micron level by airflow milling technology, and large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 20 kg / h, the gas pressure in the milling chamber is 0.6MPa, the gas temperature in the milling chamber is 150℃, the nozzle gas velocity is 1200 m / s, and the classification wheel speed is 8000rpm. The precursor particles are prepared by screening; Step (2) Solvent coating preparation S21, styrene monomer and sodium sulfonate styrene monomer as raw materials are added to NMP (the volume ratio of styrene to NMP is 5:1) in a mass ratio of 5:3 and mixed; S22: adding 6.25wt% of benzoyl peroxide and 6.25wt% of azobisisobutyronitrile to the mixed monomers, and stirring continuously at a temperature of 80°C to cause a polymerization reaction. After the reaction is completed for 3 hours, the mixture is dialyzed against water for 48 hours, vacuum dried, extracted with toluene, dissolved in ethanol, filtered, dried, and other post-treatment steps are performed to remove unreacted monomers and impurities, thereby obtaining a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone at a mass ratio of 3.5:1 to form a uniform coating solution; S24 adding the precursor material obtained by raw material pretreatment into the coating solution at a mass ratio of 3:1, stirring at a speed of 350 rpm for 1.5 hours, and after the solvent evaporates, the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer; Step (3) In-situ polymerization coating S31 Add the solvent-coated graphite particles into 30% H2O2 at a mass ratio of 2:1, stirring at 200 rpm for 0.5 h; S32 adding the oxidized graphite particles into a 4 g / mL phenol aqueous solution at 70° C. in a mass ratio of 4.5:1, stirring at a speed of 200 rpm for 10 min, so that the phenol and the graphite surface are fully infiltrated; S33 then drips formaldehyde solution (37% concentration, 0.5:1 molar ratio to phenol), and adds sodium hydroxide (0.03:1 molar ratio to phenol) as a catalyst, and stirs for 1.5 h to initiate the in-situ polymerization reaction of phenolic resin, completely covering the end faces and active sites on the graphite surface; S34 Finally, hexamethylenetetramine (the amount added is 10wt% of the total amount of the polymerized monomers) is added to the solution to cure the phenolic resin at a temperature of 140°C. After the curing is complete, the sample is washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating; Step (4) Post-graphitization treatment S41: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, performing electric heating for pyrolysis granulation according to the first part of heating rate of 5°C / min, the end temperature of 200°C, stirring for 1h; the second part of heating rate of 5°C / min, the key temperature of 400°C, stirring for 2h; S42 adds carbon nanotubes and asphalt to the preliminary granulation product (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.1:1), and follows the heating curve: the heating rate of the first part is 7℃ / min, the end temperature is 100℃, and stirring is 1h; the heating rate of the second part is 7℃ / min, the key temperature is 200℃, and stirring is 1h for secondary granulation. After the completion, the particle morphology is sphericalized by mechanical treatment. The ball milling speed of the mechanical ball milling is 250rpm, the ball milling time is 1h, and the ball-to-material ratio is 3:1; S43: placing the graphite particles after secondary granulation in a microwave reactor, adjusting the reactor to a suitable working state, including microwave frequency, power, etc., starting the microwave generator, and heating the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained (the SEM test results are shown in FIG. Figure 2As shown), the microwave frequency is: 2 GHz, the microwave initial power is: 600 W, the heating time (initial) is: 30 min, the microwave power (later) is: 1000 W, the heating time (later) is: 1 h, and the graphitization temperature is 2800 ° C.
[0045] Example 2
[0046] Step (1) Pretreatment of coke-like raw materials According to the mass ratio of 1:1, high-purity, high-crystallinity petroleum coke and needle coke are taken as the basic raw materials, 6wt% of acetylene black is added as conductive particles, and the raw materials are crushed to micron level by airflow milling technology. Large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 30 kg / h, the gas pressure in the milling chamber is 0.65 MPa, the gas temperature in the milling chamber is 175℃, the nozzle gas velocity is 1400 m / s, and the classifying wheel speed is 9000 rpm. The precursor particles are prepared by screening; Step (2) Solvent coating preparation S21 Styrene monomer and sodium sulfonate styrene monomer are added as raw materials in a mass ratio of 5.5:4 to NMP (the volume ratio of styrene to NMP is 5.4:1) and mixed; S22: adding an appropriate amount of 7 wt % benzoyl peroxide and 7 wt % azobisisobutyronitrile to the mixed monomers, and stirring continuously at a temperature of 90° C. to cause a polymerization reaction. After the reaction is completed for 4 hours, the mixture is dialyzed against water for 48 hours, vacuum dried, extracted with toluene, dissolved in ethanol, filtered, dried, and other post-treatment steps are performed to remove unreacted monomers and impurities, thereby obtaining a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone at a mass ratio of 3.5:1 to form a uniform coating solution; S24 adding the precursor material obtained by raw material pretreatment to the coating solution at a mass ratio of 3:1, stirring at a speed of 380 rpm for 2 hours, and after the solvent evaporates, the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer; Step (3) In-situ polymerization coating S31: Add the solvent-coated graphite particles into 30% H2O2 at a mass ratio of 2:1, stirring at 300 rpm for 1 h; S32: adding the oxidized graphite particles to a 5 g / mL phenol aqueous solution at 70°C in a mass ratio of 5:1, stirring at a speed of 300 rpm for 20 min to allow the phenol to fully infiltrate the graphite surface; S33 then added formaldehyde (37% concentration, 0.8:1 molar ratio to phenol) dropwise, and added sodium hydroxide (0.03:1 molar ratio to phenol) as a catalyst solution, and stirred for 1.5 h to initiate the in-situ polymerization reaction of the phenolic resin, completely covering the end faces and active sites on the graphite surface; S34 Finally, hexamethylenetetramine was added to the solution to cure the phenolic resin (the amount added was 11wt% of the total amount of the polymerized monomers). After the curing was complete at 145°C, the sample was washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating. Step (4) Post-graphitization treatment S41: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, heating the first part at a rate of 6°C / min, the end temperature at 215°C, and stirring for 2h; and heating the second part at a rate of 6°C / min, the key temperature at 425°C, and stirring for 4h for electric heating to perform pyrolysis granulation; S42: Add carbon nanotubes and asphalt to the preliminary granulation product (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.1:1), and follow the heating curve: the heating rate of the first part is 8℃ / min, the end temperature is 115℃, and stirring is 2h; the heating rate of the second part is 8℃ / min, the key temperature is 225℃, and stirring is 2h for secondary granulation. After the completion, the particle morphology is sphericalized by mechanical treatment. The ball milling speed of the mechanical ball milling is 300rpm, the ball milling time is 2h, and the ball-to-material ratio is 4:1; S43 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts the microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained. The microwave frequency is: 2.3GHz, the initial microwave power is: 650W, the heating time (initial) is: 40min, the microwave power (later) is: 1100W, the heating time (later) is 1.5h, and the graphitization temperature is 2900℃.
[0047] Example 3
[0048] Step (1) Pretreatment of coke-like raw materials According to the mass ratio of 1:1, high-purity, high-crystallinity petroleum coke and needle coke are taken as the basic raw materials, 7wt% of acetylene black is added as conductive particles, and the raw materials are crushed to micron level by airflow milling technology. Large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 40 kg / h, the gas pressure in the milling chamber is 0.7MPa, the gas temperature in the milling chamber is 200℃, the nozzle gas velocity is 1600 m / s, and the classification wheel speed is 10000 rpm. The precursor particles are prepared by screening; Step (2) Solvent coating preparation S21 Styrene monomer and sodium sulfonate styrene monomer are added as raw materials in a mass ratio of 6.5:5 to NMP (the volume ratio of styrene to NMP is 4.7:1) and mixed; S22: adding an appropriate amount of 7.25wt% benzoyl peroxide and 7.25wt% azobisisobutyronitrile to the mixed monomers, and stirring continuously at a temperature of 95°C to cause a polymerization reaction. After the reaction is completed for 5 hours, the mixture is dialyzed against water for 48 hours, vacuum dried, extracted with toluene, dissolved in ethanol, filtered, dried, and other post-treatment steps are performed to remove unreacted monomers and impurities, thereby obtaining a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone at a mass ratio of 3.8:1 to form a uniform coating solution; S24 adding the precursor material obtained by raw material pretreatment into the coating solution at a mass ratio of 3:1.5, stirring at a speed of 390 rpm for 2.5 hours, and after the solvent evaporates, the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer; Step (3) In-situ polymerization coating S31: Add the solvent-coated graphite particles into 30% H2O2 at a mass ratio of 1.8:1, stirring at 400 rpm for 1.5 h; S32: adding the oxidized graphite particles to a 5.5 g / mL phenol aqueous solution at 70°C in a mass ratio of 4.8:1, stirring at a speed of 400 rpm for 40 min to fully wet the phenol and graphite surface; S33 then added formaldehyde (37% concentration, 1:1 molar ratio with phenol), and added sodium hydroxide (0.03:1 molar ratio with phenol) as a catalyst solution, and stirred for 1.5 h to initiate the in-situ polymerization reaction of the phenolic resin, completely covering the end faces and active sites on the graphite surface; S34 Finally, hexamethylenetetramine was added to the solution to cure the phenolic resin (the amount added was 12 wt% of the total amount of the polymerized monomers). After the curing was complete at 150°C, the sample was washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating. Step (4) Post-graphitization treatment S41: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, heating the first part at a rate of 7°C / min, the end temperature at 240°C, and stirring for 3 hours; and heating the second part at a rate of 7°C / min, the key temperature at 475°C, and stirring for 6 hours for electric heating to perform pyrolysis granulation; S42: Add carbon nanotubes and asphalt to the preliminary granulation product (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.15:1), and follow the heating curve: the heating rate of the first part is 9℃ / min, the end temperature is 130℃, and stirring is 3h; the heating rate of the second part is 9℃ / min, the key temperature is 275℃, and stirring is 3h for secondary granulation. After the completion, the particle morphology is sphericalized by mechanical treatment. The ball milling speed of the mechanical ball milling is 350rpm, the ball milling time is 3h, and the ball-to-material ratio is 5:1; S43 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts the microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained. The microwave frequency is: 2.75GHz, the initial microwave power is: 750W, the heating time (initial) is: 50min, the microwave power (later) is: 1400W, the heating time (later) is 2h, and the graphitization temperature is 3000℃.
[0049] Example 4
[0050] Step (1) Pretreatment of coke-like raw materials High-purity, high-crystallinity petroleum coke and needle coke are taken as basic raw materials in a mass ratio of 1:1, and 8wt% of acetylene black is added as conductive particles. The raw materials are crushed to micron level by airflow milling technology, and large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 50kg / h, the gas pressure in the milling chamber is 0.8MPa, the gas temperature in the milling chamber is 250℃, the nozzle gas velocity is 1800 m / s, and the classifying wheel speed is 12000rpm. The precursor particles are prepared by screening; Step (2) Solvent coating preparation S21 Styrene monomer and sodium sulfonate styrene monomer are added as raw materials in a mass ratio of 5:4 to NMP (the volume ratio of styrene to NMP is 5.6:1) and mixed; S22: adding an appropriate amount of 7.5wt% benzoyl peroxide and 7.5wt% azobisisobutyronitrile to the mixed monomers, and continuously stirring at a temperature of 100°C to cause a polymerization reaction. After the reaction is completed for 6 hours, the mixture is dialyzed against water for 48 hours, vacuum dried, extracted with toluene, dissolved in ethanol, filtered, dried, and other post-treatment steps are performed to remove unreacted monomers and impurities, thereby obtaining a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone at a mass ratio of 4:1 to form a uniform coating solution; S24 adding the precursor material obtained by raw material pretreatment into the coating solution at a mass ratio of 3.2:1.5, stirring at a speed of 400 rpm for 3 hours, and after the solvent evaporates, the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer; Step (3) In-situ polymerization coating S31: Add the solvent-coated graphite particles into 30% H2O2 at a mass ratio of 2:1, stirring at 500 rpm for 2 h; S32: adding the oxidized graphite particles to a 6 g / mL phenol aqueous solution at 70°C in a mass ratio of 5:1, stirring at a speed of 500 rpm for 60 min to allow the phenol to fully infiltrate the graphite surface; S33 then added formaldehyde (37% concentration, 1.5:1 molar ratio to phenol) dropwise, and added sodium hydroxide (0.03:1 molar ratio to phenol) as a catalyst solution, and stirred for 2 h to initiate the in-situ polymerization reaction of the phenolic resin, completely covering the end faces and active sites on the graphite surface; S34 Finally, hexamethylenetetramine was added to the solution to cure the phenolic resin (the amount added was 15wt% of the total amount of the polymerized monomers). After the curing was complete at 160°C, the sample was washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating. Step (4) Post-graphitization treatment S41: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, heating the first part at a rate of 8°C / min, the end temperature at 250°C, and stirring for 4 hours; and heating the second part at a rate of 8°C / min, the key temperature at 500°C, and stirring for 8 hours for electric heating to perform pyrolysis granulation; S42 adds carbon nanotubes and asphalt to the preliminary granulation product (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.18:1), and follows the heating curve: the heating rate of the first part is 10℃ / min, the end temperature is 150℃, and stirring is 4h; the heating rate of the second part is 10℃ / min, the key temperature is 300℃, and stirring is 4h for secondary granulation. After the completion, the particle morphology is sphericalized by mechanical treatment. The ball milling speed of the mechanical ball milling is 400rpm, the ball milling time is 4h, and the ball-to-material ratio is 6:1; S43 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts the microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained. The microwave frequency is: 3GHz, the initial microwave power is: 800W, the heating time (initial) is: 60min, the microwave power (later) is: 1500W, the heating time (later) is 3h, and the graphitization temperature is 3200℃.
[0051] Example 5
[0052] The difference between the preparation process and Example 1 is that in the in-situ polymerization coating of step (3), the oxidation treatment of step S31 is not performed.
[0053] Example 6
[0054] The difference between the preparation process and Example 1 is that in step (2) of the solvent coating preparation, an equal molar amount of styrene is used to replace sodium styrene sulfonate in step S21.
[0055] Comparative Example 1
[0056] Step (1) Pretreatment of coke-like raw materials High-purity, high-crystallinity petroleum coke and needle coke are taken as basic raw materials in a mass ratio of 1:1, and 5wt% of acetylene black is added as conductive particles. The raw materials are crushed to micron level by airflow milling technology, and large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 20 kg / h, the gas pressure in the milling chamber is 0.6MPa, the gas temperature in the milling chamber is 150℃, the nozzle gas velocity is 1200 m / s, and the classification wheel speed is 8000rpm. The precursor particles are prepared by screening; Step (2) Solvent coating preparation S21, styrene monomer and sodium sulfonate styrene monomer as raw materials are added to NMP (the volume ratio of styrene to NMP is 5:1) in a mass ratio of 5:3 and mixed; S22: adding 6.25wt% of benzoyl peroxide and 6.25wt% of azobisisobutyronitrile to the mixed monomers, and stirring continuously at a temperature of 80°C to cause a polymerization reaction. After the reaction is completed for 3 hours, the mixture is dialyzed against water for 48 hours, vacuum dried, extracted with toluene, dissolved in ethanol, filtered, dried, and other post-treatment steps are performed to remove unreacted monomers and impurities, thereby obtaining a sodium polystyrene sulfonate product; S23 dissolving sodium polystyrene sulfonate in N-methylpyrrolidone at a mass ratio of 3.5:1 to form a uniform coating solution; S24 The precursor material obtained by raw material pretreatment is added to the coating solution at a mass ratio of 3:1, and stirred at 350 rpm for 1.5 hours. After the solvent evaporates, the coating material is uniformly adsorbed on the surface of the precursor particles to form a uniform coating layer.
[0057] Step (3) Post-graphitization treatment S31: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, performing electric heating for pyrolysis granulation according to the first part of heating rate of 5°C / min, the end temperature of 200°C, stirring for 1h; the second part of heating rate of 5°C / min, the key temperature of 400°C, stirring for 2h; S32 adds the preliminary granulation product to Carbon nanotubes and asphalt (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.1:1), according to the heating curve: the first part of the heating rate is 7℃ / min, the end temperature is 100℃, and stirring is 1h; the second part of the heating rate is 7℃ / min, the key temperature is 200℃, and stirring is 1h for secondary granulation. After the end, the particle morphology is spheroidized by mechanical treatment to prepare supercharged artificial graphite negative electrode material. The ball milling speed of mechanical ball milling is 250rpm, the ball milling time is 1h, and the ball-to-material ratio is 3:1; S33 places the graphite particles after secondary granulation in a microwave reactor, adjusts the reactor to a suitable working state, including microwave frequency, power, etc., starts the microwave generator, and heats the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained. The microwave frequency is: 2GHz, the initial microwave power is: 600W, the heating time (initial) is: 30min, the microwave power (later) is: 1000W, the heating time (later) is 1h, and the graphitization temperature is 2800℃.
[0058] Comparative Example 2
[0059] Step (1) Pretreatment of coke-like raw materials High-purity, high-crystallinity petroleum coke and needle coke are taken as basic raw materials in a mass ratio of 1:1, and 5wt% of acetylene black is added as conductive particles. The raw materials are crushed to micron level by airflow milling technology, and large particles and impurities are removed by screening process to obtain the precursor with the required particle size. In the airflow milling technology, the raw material feed rate is 20kg / h, the gas pressure in the milling chamber is 0.6MPa, the gas temperature in the milling chamber is 150℃, the nozzle airflow velocity is 1200 m / s, and the classification wheel speed is 8000rpm. The precursor particles are prepared by screening; Step (2) In-situ polymerization coating S31 Add the solvent-coated graphite particles into 30% H2O2 at a mass ratio of 2:1, stirring at 200 rpm for 0.5 h; S32 adding the oxidized graphite particles into a 4 g / mL phenol aqueous solution at 70° C. in a mass ratio of 4.5:1, stirring at a speed of 200 rpm for 10 min, so that the phenol and the graphite surface are fully infiltrated; S33 then drips formaldehyde solution (37% concentration, 0.5:1 molar ratio to phenol), and adds sodium hydroxide (0.03:1 molar ratio to phenol) as a catalyst, and stirs for 1.5 h to initiate the in-situ polymerization reaction of phenolic resin, completely covering the end faces and active sites on the graphite surface; S34 Finally, hexamethylenetetramine (the amount added is 10wt% of the total amount of the polymerized monomers) is added to the solution to cure the phenolic resin at a temperature of 140°C. After the curing is complete, the sample is washed and separated, and dried to obtain a modified artificial graphite negative electrode material with uniform in-situ polymerization coating; Step (3) Post-graphitization treatment S31: putting the dried coated graphite particles into a reaction kettle, and in an inert gas atmosphere, performing electric heating for pyrolysis granulation according to the first part of heating rate of 5°C / min, the end temperature of 200°C, stirring for 1h; the second part of heating rate of 5°C / min, the key temperature of 400°C, stirring for 2h; S32: Add carbon nanotubes and asphalt to the preliminary granulation product (the mass ratio of the two is 1:1, and the mass ratio of the total amount of the mixture to the pyrolysis granulation is 0.1:1), and follow the heating curve: the heating rate of the first part is 7℃ / min, the end temperature is 100℃, and stirring is 1h; the heating rate of the second part is 7℃ / min, the key temperature is 200℃, and stirring is 1h for secondary granulation. After the completion, the particle morphology is sphericalized by mechanical treatment. The ball milling speed of the mechanical ball milling is 250rpm, the ball milling time is 1h, and the ball-to-material ratio is 3:1. S33: placing the graphite particles after secondary granulation in a microwave reactor, adjusting the reactor to a suitable working state, including microwave frequency, power, etc., starting the microwave generator, and heating the graphite particles. By controlling the microwave power and heating time, the graphite particles gradually reach the graphitization temperature. After graphitization, a 6C supercharged artificial graphite negative electrode material is obtained (the SEM test results are shown in FIG. Figure 2 As shown), the microwave frequency is: 2 GHz, the microwave initial power is: 600 W, the heating time (initial) is: 30 min, the microwave power (later) is: 1000 W, the heating time (later) is: 1 h, and the graphitization temperature is 2800 ° C.
[0060] Comparative Example 3
[0061] The difference between the preparation process and Example 1 is that in step (4) graphitization post-treatment, step S43 adopts conventional graphitization treatment method instead of microwave treatment, specifically: The graphite particles after the secondary granulation are placed in an Acheson furnace and heated to 2800° C., kept at this temperature for 1 hour, and then cooled naturally to obtain an artificial graphite negative electrode material.
[0062] Comparative Example 4
[0063] The difference between the preparation process and Example 1 is that the large-sized precursor particles obtained by pretreating the charred raw material in step (1) have a particle size D50 of 15 μm.
[0064] Test example: Preparation of a negative electrode sheet. Supercharged artificial graphite negative electrode material, polyvinylidene fluoride and carbon nanotubes (mass ratio of 80%: 15%: 5%) are mixed into a slurry. Then it is repeatedly rolled into a thin sheet with a glass rod, and then the thin sheet is made into a circular carbon sheet with a diameter of 10mm with a puncher. Finally, the carbon sheet is placed in a 110℃ vacuum drying oven and dried for 2h and then taken out. After drying, the electrode sheet is subjected to a short-term heat treatment and kept at 150℃ for 1 hour to prepare a negative electrode sheet.
[0065] An electrochemical device. The prepared negative electrode sheet is used as the working electrode, the metal lithium sheet is used as the counter electrode, and the diaphragm is purchased from Shenzhen Kejing Zhida Technology Co., Ltd. The material is polyethylene, the diameter is Φ18 mm, the thickness is 16 μm, and the electrolyte is 1 mol·L -1LiPF6 is used as the solute, and EC, EMC, and DMC are used as the solvents in a volume ratio of 1:1:1. Oxygen and water are removed in the glove box before assembly. The assembly sequence is as follows: lay the positive electrode shell open upward on the platform; clamp the nickel foam as the current collector and place it in the positive electrode shell; then put the electrode sheet in, and inject 100 μL of electrolyte between the working electrode sheet and the diaphragm, and between the lithium sheet and the diaphragm; then, move the battery horizontally to the button battery sealing machine and apply a pressure of 12 MPa for 10 s to complete the battery packaging, and obtain an electrochemical device containing the lithium-ion battery.
[0066] The 6C supercharged artificial graphite negative electrode materials obtained in Examples 1-6 and the products of Comparative Examples 1-4, i.e., their lithium ion batteries, were tested. The specific testing methods are as follows: 6C charging lithium deposition test The electrochemical devices prepared in the embodiments and comparative examples were subjected to a complete charge and discharge cycle, and their SOC was calibrated. Under a constant temperature environment, the battery was tested at a 6C charging rate using a battery charge and discharge test system while meeting 10% to 80% SOC. After charging, the battery was subjected to an EIS test using an electrochemical workstation. By analyzing the characteristic changes in the high-frequency intercept and semicircle size in the EIS curve, it was found that the electrochemical process inside the battery was very stable, and no lithium precipitation reaction occurred. Combined with physical observation, the surface morphology of the negative electrode was observed under a microscope, and the inspection results showed that there were no white spots or layered structures formed by lithium precipitation. The above test results show that there is no lithium precipitation in the battery, and the charging performance is stable.
[0067] Rate performance and cycle performance test Use HTB2060 battery charge and discharge test instrument, set the charge and discharge voltage to 0-2.5 V at room temperature, and perform constant current charge and discharge test at a rate of 6C.
[0068] Compacted density test The samples prepared in the embodiments and comparative examples were tested at room temperature using a GURLEY porosity detector produced by TLS of Germany to obtain their respective compacted densities.
[0069] The sphericity calculation formula is: Q=4πS / L2, where S represents the equivalent circular area of the particle projection and L represents the actual circumference of the particle. The larger the sphericity value (closer to 1), the more rounded the morphology. The particle morphology characteristic value Q50 (the sphericity corresponding to the cumulative sphericity distribution percentage of a sample reaches 50%) is used to represent the sphericity of the material.
[0070] The performance index data of the test methods not mentioned are all measured by conventional test methods used by those skilled in the art.
[0071] Table 1 Rate performance test results
[0072] It can be seen from Table 1 that the 6C artificial super-charged graphite negative electrode material prepared in the embodiment has very good gram capacity and excellent discharge capacity retention rate after 3000 cycles, and the result satisfies the gram capacity>330mAh / g, and the better result can even reach 355mAh / g or more; when the number of cycles reaches 3000 times, the discharge capacity is not less than 80% of the initial capacity, and is higher than the test results of the samples prepared in the comparative example. Since the embodiment adds excellent conductive particles acetylene black in the pretreatment of the raw materials, the addition of acetylene black as conductive particles can significantly improve the conductive properties of the graphite negative electrode material. Acetylene black has excellent conductivity and liquid absorption, can increase the electron transmission channel inside the material, reduce internal resistance, and improve the charge and discharge efficiency and power density of the battery; the addition of high-purity, high-crystallinity raw materials and conductive particles, as well as precise particle size control, jointly improve the electrochemical properties of the graphite negative electrode material. At the same time, the double-layer coating is formed by solvent polymerization and in-situ polymerization, the thickness and uniformity of the coating layer are precisely controlled, the stability and durability of the coating layer are improved, and the electrochemical performance of the graphite negative electrode material can be further enhanced; and the microwave heating graphitization step is creatively added in the graphitization post-processing process. Microwave heating can more fully activate the carbon atoms in the graphite particles, promote their transformation to graphite structure, and improve the degree of graphitization. This helps to improve the conductivity, thermal stability and chemical stability of the negative electrode material.
[0073] Table 2 Compacted density test results
[0074] It can be seen from Table 2 that the pole piece compaction density of the 6C artificial super-filled graphite negative electrode material prepared in the embodiment is greater than the pole piece compaction density ratio of the super-filled graphite negative electrode material prepared in the comparative example, and both are greater than 1.60g / cc. The solvent coating can be carried out by dissolving the coating material in a solvent and then mixing it with the graphite negative electrode material so that the coating material is evenly distributed on the graphite surface, which helps to reduce the pores and defects inside the material, thereby improving the compaction density. In the embodiment, an in-situ polymerization method is also used for composite coating. The in-situ polymerization method directly initiates a polymerization reaction on the surface of the graphite negative electrode material to form a more uniform and dense coating layer, which is tightly combined with the graphite surface, which helps to improve the compaction density, reduce the interface resistance, and improve the transmission efficiency of electrons and ions, thereby effectively improving the conductivity, cycle stability and fast charging performance of the graphite negative electrode material.
[0075] The combination of solvent coating and in-situ coating can effectively inhibit the expansion and contraction of graphite during the charge and discharge process, reduce structural damage, and thus improve the cycle life and stability of the material. At the same time, it can effectively improve the sphericity of the negative electrode material product, and its graphitization degree is also significantly improved, which can significantly enhance the electrochemical performance of artificial graphite negative electrode materials.
[0076] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A 6C supercharged artificial graphite negative electrode material, characterized in that include: The gram capacity of the 6C supercharged artificial graphite negative electrode material is greater than 330 mAh / g; the compaction density of the electrode is greater than or equal to 1.60 g / cc; 10%~80% SOC meets 6C charging without lithium deposition; after 3000 cycles, the discharge capacity retention rate is ≥80%.
2. A 6C supercharged artificial graphite negative electrode material according to claim 1, characterized in that: Include at least one of the following characteristics: (1) The gram capacity of the 6C supercharged artificial graphite negative electrode material is greater than 350 mAh / g; (2) The electrode compaction density is greater than 1.80 g / cc; (3) When the 6C supercharged artificial graphite negative electrode material is cycled 3000 times, the discharge capacity retention rate is greater than 86%; (4) The initial efficiency of the 6C supercharged artificial graphite negative electrode material is greater than 93%; (5) The specific surface area of the 6C supercharged artificial graphite negative electrode material is 0.5~3m 2 / g; (6) The particle size D50 of the 6C supercharged artificial graphite negative electrode material is 5-13 μm; (7) The sphericity of the 6C supercharged artificial graphite negative electrode material is greater than 0.85; (8) The graphitization degree of the 6C supercharged artificial graphite negative electrode material is ≥ 94%.
3. A method for preparing the 6C supercharged artificial graphite negative electrode material according to claim 1, characterized in that include: The 6C supercharged artificial graphite negative electrode material is prepared by using the pretreated charred raw material through solvent coating and in-situ polymerization coating composite coating, and then through graphitization post-treatment.
4. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 3, characterized in that: The preparation process includes at least one of the following features (1) to (3): (1) The coke-like raw material includes at least one of petroleum coke, needle coke, asphalt coke or anthracite; (2) The pretreatment includes air flow milling, wherein the feed rate of the raw material is 20-50 kg / h, the gas pressure in the mill chamber is 0.6-0.8 MPa, the gas temperature in the mill chamber is 150-250°C, the nozzle air flow velocity is 1200-1800 m / s, and the classifying wheel speed is 8000-12000 rpm; (3) The particle size D50 of the coke-like raw material after the pretreatment is: 3~10μm; The pretreatment of the coke-like raw material comprises: Select high-purity, high-crystallinity coke-like raw materials as the basic raw materials, add an appropriate amount of conductive particles, use airflow grinding technology to crush the raw materials to micron level, remove large particles and impurities through screening process, and obtain the precursor with the required particle size; The conductive particles include at least one of carbon nanotubes, conductive carbon black, acetylene black, graphite particles, graphene, metal powder or carbon fiber species.
5. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 3, characterized in that: The solvent coating comprises: Dissolving the coating material in an organic solvent to form a uniform coating solution, and adding the precursor material obtained by pre-treatment of the raw material for coating; The solvent coating process comprises at least one of the following features (1) to (4): (1) The coating material is sodium polystyrene sulfonate; (2) The organic solvent includes at least one of deionized water, N-methylpyrrolidone or dimethylformamide; (3) The mass ratio of the coating material to the solvent is 1:(10-20); (4) The mass ratio of the precursor particles to the coating solution is (2-5):
1.
6. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 5, characterized in that: The preparation of the coating material comprises: Styrene monomer and sodium sulfonate styrene monomer are mixed and polymerized in an initiator system to obtain a sodium polystyrene sulfonate product; The coating material preparation process includes at least one of the following features (1) to (4): (1) The mass ratio of the styrene monomer to the sodium sulfonate styrene monomer is: (3-6): 1; (2) The initiator comprises at least one of benzoyl peroxide and azobisisobutyronitrile; (3) The polymerization reaction temperature is 60-85°C; (4) The polymerization reaction time is 3 to 6 hours.
7. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 3, characterized in that: The in-situ polymerization coating comprises: The product coated by the solvent method is first subjected to oxidation treatment, and then added to a polymerization system containing phenolic and aldehyde compounds to initiate in-situ polymerization; and then a curing agent is added to perform curing treatment to obtain an in-situ polymerization coated product; The in-situ polymerization coating process comprises at least one of the following features (1) to (10): (1) The reagent used in the oxidation treatment includes H2O2; (2) The phenolic compound includes at least one of phenol, diphenol, naphthol and cresol; (3) The aldehyde compound includes at least one of formaldehyde, furfural, benzaldehyde and isobutylaldehyde; (4) The mass ratio of the product coated by the solvent method to the oxidant used for oxidation treatment is: (1-4): 1; (5) The mass ratio of the solution of the phenolic compound to the product coated by the solvent method is: 1:(3-6); (6) The polymerization system further comprises an initiator, specifically an acidic or basic initiator; (7) The curing agent includes at least one of hexamethylenetetramine, diethylaminopropylamine, trimethylhexamethylenediamine, and dihexyltriamine; (8) The mass ratio of the curing agent to the product after solvent coating is: (0.1~0.4):
1.
8. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 3, characterized in that: The graphitization post-treatment comprises: The composite coated product is first subjected to pyrolysis granulation, then additives are added, secondary granulation is performed at high temperature, followed by spheroidization shaping, and finally graphitization treatment is performed to obtain 6C supercharged artificial graphite negative electrode material; The graphitization post-treatment process includes at least one of the following features (1) to (6): (1) The temperature curve in the pyrolysis granulation is: the first part has a heating rate of 5-8°C / min, an end temperature of 200-250°C, and stirring for 1-4 hours; the second part has a heating rate of 5-8°C / min, a key temperature of 400-500°C, and stirring for 2-8 hours; (2) The additive includes at least one of carbon nanotubes, conductive carbon black, asphalt or phenolic resin; (3) The mass ratio of the additive to the composite coated product is: (0.05-0.2):1; (4) The temperature curve of the secondary granulation is: the first part has a heating rate of 7-10°C / min, an end temperature of 100-150°C, and stirring for 1-4h; the second part has a heating rate of 7-10°C / min, a key temperature of 200-300°C, and stirring for 1-4h; (5) The ball milling speed of the mechanical ball mill is 250-400 rpm, the ball milling time is 1-4 hours, and the ball-to-material ratio is (3-6):1; (6) The graphitization treatment includes microwave graphitization treatment; preferably, in the microwave graphitization, the microwave frequency is: 2~3GHz, the microwave initial power is: 600~800W, the heating time (initial) is: 30~60min, the microwave power (later) is: 1000~1500W, the heating time (later) is: 1~3h, and the graphitization temperature is 2800~3200℃.
9. The method for preparing a 6C supercharged artificial graphite negative electrode material according to claim 3, characterized in that: The ratio of the particle size D50 of the 6C supercharged artificial graphite negative electrode material to the pretreated coke-like raw material D50 is 1-2.
10. An application of the 6C supercharged artificial graphite negative electrode material according to claim 1 in the preparation of battery negative electrode materials, negative electrode sheets, and energy storage devices.